If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6n + -0.7 = 11 Reorder the terms: -0.7 + 6n = 11 Solving -0.7 + 6n = 11 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '0.7' to each side of the equation. -0.7 + 0.7 + 6n = 11 + 0.7 Combine like terms: -0.7 + 0.7 = 0.0 0.0 + 6n = 11 + 0.7 6n = 11 + 0.7 Combine like terms: 11 + 0.7 = 11.7 6n = 11.7 Divide each side by '6'. n = 1.95 Simplifying n = 1.95
| 10+n=25 | | -18x^2+51x+8=0 | | X^2+6x+64=48 | | 9x^4-64=0 | | 4c^2+7x-15=0 | | 15+n=6 | | 3x^4-7x^2=0 | | (4x+2)-x=(2x-10) | | 9(2+v)+35v=14v | | .5x(x+4)=16 | | 69=12 | | 2a+4b=226 | | 8(4+v)+34v=14v | | -2.3q+16=-5q-3 | | x^2+6x-24.01=0 | | 10*x+4=12*x-16 | | 3+2(x-1)=4x | | 3+2n-6=25 | | 8z+11=7z+5 | | 4(12n-6)=6(-4+5n)+18n | | 2x-2.8-2.4x+2.6x-5= | | 6(-3-x)-2*x=14 | | 6sec^2(0)-2sec^2(0)= | | 4x^4+21x^2-18=0 | | -7=7-(8-a) | | Y=50+1x | | yz^2-z^2+5+3yz-3z^2+4yz= | | 16=7-(b+9) | | (x-1)(x+3)=(x+2)(x-3) | | -2*x+8=-16 | | -3x+4y=46 | | 5y-7y-6=2 |